Risk awareness model for security and privacy in social networking sites from the users’ perspective - Abiodun, Balogun Kamoru (2021)
The ability to interact with other people has become one of the most popular web-traffic phenomena in the digital age. There are risks connected with the Social Networking sites, which provides the potential of having victims investigated in a variety of ways to assess and limit. There are several ways for a user to prevent or minimize the degree of danger for the Social Networking sites, such as ensuring that the computer and Social Networking Sites have adequate security measures in place and limiting unnecessary clicking of unauthorized links. Besides, users can request that their profile be erased when it becomes obsolete. Being cautious about the applications is also another method of minimizing risks associated with Social Networking sites. It is also important to generate unique passwords coupled with being cautious on social media to ensure that their actions are limited. Additionally, configuring and reviewing the Social Networking sites privacy policy regularly can offer appropriate protection. Many studies show that the more a person visits a website, the more likely they are to be targeted by risk associated with Social Networking Sites. A major contribution of the study is risk awareness model development and proposed Social Networking sites Risk Meter (SNSR).